rust levels of patients in emergency medical technicians, associated factors, and resulting outcomes - Alireza Rasouli (Zanjan University of Medical Sciences and Health Services, 2024)
Background: Trust between patients and Emergency Medical Technicians (EMTs) is crucial for effective pre-hospital nursing care. Objectives: This study aimed to assess the trust levels of patients in emergency medical technicians, associated factors, and resulting outcomes. Methods: This cross-sectional study was conducted on 400 patients transported by EMTs to the emergency departments of teaching hospitals in Zanjan City during 2023-2024. Data collection tools included demographic questionnaires, the Patient Trust Questionnaire (PTQ), a Visual Analog Pain Scale (VAS-P), and a Visual Analog Scale for Anxiety (VAS-A). Data were analyzed using SPSS version 24 software. Pearson's correlation, multiple regression, and simple linear regression statistical tests were conducted, with a significance level of less than 0.05. Results: Patients had a mean (SD) trust level of 4.11 (0.92) in EMTs. Patients' trust could be predicted by factors such as the speed of EMTs' performance, reason for calling EMS, place of residence, and education (R=0.42, Adjusted R Square=0.17). The trust variable predicted anxiety, in patients. (p<0.05). Conclusion: Trust in pre-hospital care helps manage patients' mental conditions. EMTs play a crucial role in building patients' trust during emergencies.